63.9k views
0 votes
Solve for x 6 ( x − 2 ) = 8 ( x − 9 )

User Javing
by
6.4k points

2 Answers

3 votes
X = 30 aaaaaaaaaaaaaaaaaaa
User Nirit
by
5.4k points
6 votes

Answer:

x = 30

Explanation:

in order to solve for the value of x in the expression 6 ( x − 2 ) = 8 ( x − 9 )

we will first of all open the brackets and then evaluate for the value of x by combining the like terms.

from 6 ( x − 2 ) = 8 ( x − 9 )

6x -12 = 8x -72

combine the like terms

6x - 12 + 72 = 8x

-12 + 72 = 8x -6x

60 = 2x

divide both sides by the coefficient of x which is 2

60/2 = 2x/2

30 = x

x = 30

therefore the value of x in the expression 6 ( x − 2 ) = 8 ( x − 9 ) is equals to 30

User IanGSY
by
6.3k points